Evaluating Differentiated Instruction Implementation in Early Childhood Education Using the CIPP Model - Siti Rodiyah (BRIDGE : The Multidisciplinary Research Portal, 2025)
Differentiated instruction has emerged as a core pedagogical strategy for addressing learner diversity in inclusive early childhood education. This study evaluates the implementation of differentiated instruction in early childhood education institutions using the Context, Input, Process, and Product (CIPP) evaluation model. Employing a qualitative descriptive design, data were collected through interviews, classroom observations, and document analysis involving school leaders, teachers, and institutional records. Data were analyzed thematically using triangulation to ensure analytical rigor and coherence across evaluation dimensions. The findings indicate that differentiated instruction has been implemented effectively across the four CIPP components. Contextually, supportive school environments and institutional commitment facilitate instructional adaptation. Input evaluation highlights the alignment of curriculum design, learning resources, and teacher competencies with differentiated learning principles. Process evaluation reveals that instructional practices are responsive to students’ readiness, interests, and learning profiles, supported by formative assessment strategies. Product evaluation demonstrates positive outcomes in student engagement, learning motivation, confidence, participation, and early critical thinking development. Despite these strengths, challenges remain related to time management, limited access to learning resources, and uneven teacher preparedness, which affect the consistency of implementation. This study contributes to the literature on early childhood education and inclusive pedagogy by providing a systematic evaluation of differentiated instruction using a well-established program evaluation framework. The findings underscore the importance of continuous professional development, school-based learning communities, and institutional monitoring to sustain effective differentiated instruction. Overall, the study offers evidence-based insights to inform policy refinement and pedagogical practice in early childhood education across diverse educational contexts.differentiated instruction